KAJI NUMERIK DAN EKSPERIMENTAL PERPINDAHAN PANAS PADA KONDENSER BERPENDINGIN UDARA - Darmanto, Prihadi Setyo; Arjanto, Dedy Dwi; Ismail, Muhammad (Mesin, 2002)
This paper presents numerical and experimental study of the heat transfer on fins-tube heat exchanger that was employed as an air cooled condenser of the air conditioning system. In this case change of phase occurs on refrigerant side while air remain at gas phase. The proposed numerical analysis is based on the application of mass and energy balances implemented at a small control volume that is part of the condenser. The result of numerical evaluation was then compared with the experimental observation. A good agreement between experimental and numerical results was achieved and the numerical method is proposed that to be used as a tool for fins tube condenser design.